Post-stroke dysphagia: clinical and radiological outcomes and efficacy - Everton, Lisa (2021)
Upwards of 50% of stroke survivors show symptoms of swallowing impairment (dysphagia) post-stroke. Dysphagia is clinically important as it results in poorer outcomes and affects quality of life. Despite this, there are few proven treatments. In addition, the act of swallowing is intricate and complex and may be best measured using multiple outcomes.